Water Tube Boiler Pabrik Kelapa Sawit Kapasitas 45 Ton/Jam - Istianto Budhi Rahardja; Erlangga Abinanda; Ahdiat Leksi Siregar (JURNAL CITRA WIDYA EDUKASI, 2022)
The use of steam power plants in palm oil mills is still a profitable alternative to use, therefore in-depth knowledge of various matters relating to steam power generation systems is required. The main function of the boiler is to produce steam which is used in the sterilization process for processed palm oil and is also used in the clarification process of crude palm oil (CPO). Apart from the above functions, one boiler unit in the palm oil mill is also used to generate electrical energy which is used to support the production process and needs in the palm oil mill environment. In a boiler system, the readiness and conditioning of the equipment need to be considered in order to meet the planned production targets. Good efficiency needs to be maintained in a boiler, by conducting periodic inspections and checking of the components in the boiler. Then, a boiler also functions as a vital tool in a crude palm oil (CPO) processing plant.